Protective antibodies to plasmodium falciparum and immunity to malaria in an endemic area of Brazil - Tosta, Carlos Eduardo (1986)
ABSTRACT: The objective of this work was to get baseline information about the prevalence of protective antibodies against P. falciparum sporozoites and eiythrocync forms in a malaria endemic area of Brazil. These data will help us to understand the process of development of resistance against malaria and to plan strategies for programmes of vaccination in endemic areas.